PENGARUH PENGUNGKAPAN LINGKUNGAN DAN KINERJA LINGKUNGAN TERHADAP KINERJA EKONOMI YANG DIMODERASI GOOD CORPORATE GOVERNANCE - Rahmawati, Mia Ika; Subardjo, Anang (Buletin Studi Ekonomi; VOL.22.NO.2. AGUSTUS 2017 (PP 113-261), 2017)
This study aims to examine the effect of Environmental Disclosure and Environmental Performance on Economic Performance in Corporate Governance Moderation based on the results of hypothesis testing by using Multiple Linear Regression shows that the disclosure of environment and environmental performance have an effect on to economic performance. Aspects of Corporate Governance that can moderated The Effect of Environmental Disclosure and Environmental Performance on Economic Performance is Background of Culture and Ethics Independent Board of Commissioners and Proportion of Independent Commissioners, while Education Background of Board of Commissioners and Number of Meetings of Board of Commissioners can not moderate Influence of Environmental and Performance Disclosure Environment on Economic Performance. Keywords: environmental disclosure, environmental performance, corporate govenance, economic performance